A new puff modelling technique for short range dispersion applications. (8th February 2011) - Thomson, David J.; Jones, Andrew R.
A puff model is proposed for short range dispersion applications. The model aims to reproduce the results of a stochastic Lagrangian particle model while avoiding to a large extent the noise which is often present in Lagrangian particle models. Part of the dispersion is modelled through the growth of the puffs while part is treated by a random motion of the puff centres. Comparisons with a Lagrangian particle model are presented for an idealised convective boundary layer. Also, the performance of the model in simulating the Kincaid experiment is described. The results are comparable with the best performing models for this dataset.